La saggezza del limite. Dal pathos del nulla al governo della contingenza - Natoli, Salvatore (Bollettino Filosofico, 2015)
Western nihilism could be considered as the result of secularization, and secularization as the horizon of Western philosophy. The dynamics of contemporary society coincides with the process of self-affirmation of man, and this idea moves together with the progressive abandonment of the reference to the transcendence. The main reason for this process of secularization is the disappointment of a missed salvation. So, time has changed its direction, and today we can see the triumph of a new carpe diem. But the destination of man is being able to live in a changing, uncertain, unknown time, knowing in advance that this uncertainty could be his real fate.